Constructing generative logical models for optimisation problems using domain knowledge - Srinivasan, Ashwin; Vig, Lovekesh; Shroff, Gautam (Machine learning, 2020)
In this paper we seek to identify data instances with a low value of some objective (or cost) function. Normally posed as optimisation problems, our interest is in problems that have the following characteristics: (a) optimal, or even near-optimal solutions are very rare; (b) it is expensive to obtain the value of the objective function for large numbers of data instances; and (c) there is domain knowledge in the form of experience, rules-of-thumb, constraints and the like, which is difficult to translate into the usual constraints for numerical optimisation procedures. Here we investigate the use of Inductive Logic Programming (ILP) to construct models within a procedure that progressively attempts to increase the number of near-optimal solutions. Using ILP in this manner requires a change in focus from discriminatory models (the usual staple for ILP) to generative models. Using controlled datasets, we investigate the use of probability-sampling of solutions based on the estimated cost of clauses found using ILP. Specifically, we compare the results obtained against: (a) simple random sampling; and (b) generative deep network models that use a low-level encoding and automatically construct higher-level features. Our results suggest: (1) Against each of the alternatives, probability-sampling from ILP-constructed models contain more near-optimal solutions; (2) The key to the effectiveness of ILP-constructed models is the availability of domain knowledge. We also demonstrate the use of ILP in this manner on two real-world problems from the area of drug-design (predicting solubility and binding affinity), using domain knowledge of chemical ring structures and functional groups. Taken together, our results suggest that generative modelling using ILP can be very effective for optimisation problems where: (a) the number of training instances to be used is restricted, and (b) there is domain knowledge relevant to low-cost solutions.